Generating usable knowledge through an experimental approach to public administration - Jilke, Sebastian; Walle, Steven Van De; Kim, Soonhee (2016)
This introduction to the symposium on experimental methods in public administration shows how using experimental methods generates not only research that is empirically credible, but also relates to the real world of public administration. The ten articles in the symposium subject classic public administration theories or hypotheses that have been generated in nonexperimental research to rigorous testing using experimental methods. The first group of articles consists of studies with citizens who interact with government. The second group consists of three studies with public officials. - Reproduced.
Keywords: Public administration